Advancing Stroke Recovery Through Improved Articulation of Nonpharmacological Intervention Dose. Issue 2 (February 2021) - Hayward, Kathryn S.; Churilov, Leonid; Dalton, Emily J.; Brodtmann, Amy; Campbell, Bruce C.V.; Copland, David; Dancause, Numa; Godecke, Erin; Hoffmann, Tammy C.; Lannin, Natasha A.; McDonald, Matthew W.; Corbett, Dale; et al.
Abstract : Dose articulation is a universal issue of intervention development and testing. In stroke recovery, dose of a nonpharmaceutical intervention appears to influence outcome but is often poorly reported. The challenges of articulating dose in nonpharmacological stroke recovery research include: (1) the absence of specific internationally agreed dose reporting guidelines; (2) inadequate conceptualization of dose, which is multidimensional; and (3) unclear and inconsistent terminology that incorporates the multiple dose dimensions. To address these challenges, we need a well-conceptualized and consistent approach to dose articulation that can be applied across stroke recovery domains to stimulate critical thinking about dose during intervention development, as well as promote reporting of planned intervention dose versus actually delivered dose. We followed the Design Research Paradigm to develop a framework that guides how to articulate dose, conceptualizes the multidimensional nature and systemic linkages between dose dimensions, and provides reference terminology for the field. Our framework recognizes that dose is multidimensional and comprised of a duration of days that contain individual sessions and episodes that can be active (time on task) or inactive (time off task), and each individual episode can be made up of information about length, intensity, and difficulty. Clinical utility of this framework was demonstrated via hypothetical application to preclinical and clinical domains of stroke recovery. The suitability of the framework to address dose articulation challenges was confirmed with an international expert advisory group. This novel framework provides a pathway for better articulation of nonpharmacological dose that will enable transparent and accurate description, implementation, monitoring, and reporting, in stroke recovery research. Abstract : Supplemental Digital Content is available in the text.